2020
DOI: 10.4254/wjh.v12.i9.533
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications, diagnosis, and management of diabetes in patients with chronic liver diseases

Abstract: Diabetes mellitus (DM) negatively affects the development and progression of chronic liver diseases (CLD) of various etiologies. Concurrent DM and CLD are also associated with worse clinical outcomes with respect to mortality, the occurrence of hepatic decompensation, and the development of hepatocellular carcinoma (HCC). Unfortunately, early diagnosis and optimal treatment of DM can be challenging, due to the lack of established clinical guidelines as well as the medical complexity of this patient population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 238 publications
(241 reference statements)
1
25
0
Order By: Relevance
“…In this study, increase in both liver enzymes' activities: ALT and AST as well as reduced total [8]. Suppressed activities of these enzymes and elevated level of total protein in diabetic rats fed various formulated seed varieties suggest their ability in protecting and enhancing liver function.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In this study, increase in both liver enzymes' activities: ALT and AST as well as reduced total [8]. Suppressed activities of these enzymes and elevated level of total protein in diabetic rats fed various formulated seed varieties suggest their ability in protecting and enhancing liver function.…”
Section: Discussionsupporting
confidence: 49%
“…Diabetes mellitus has been found to be strongly associated with the development and progression of liver injury with worse clinical outcomes, including; reduced survival, more severe liver failure-related complications etc [8]. Liver functions as a "glucostat".…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have shown that 21%-78% of diabetic patients present pathological liver changes, such as hepatic steatosis, fatty acid deposition, and fibrosis [ 6 , 7 ]. It has been reported that insulin resistance (IR) and T2DM-induced metabolic syndrome were risk factors for liver damage, such as nonalcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH), and liver fibrosis [ 8 ]. Due to the vital link between T2DM and progressive liver disease, in-depth research on the pathogenesis of diabetic liver disease is needed.…”
Section: Introductionmentioning
confidence: 99%
“…115 AGI may benefit patients with cirrhosis and diabetes as they reduce postprandial hyperglycemia and glycemic variation. 116 Another advantage of AGI is that they may have a beneficial effect in hepatic encephalopathy by decreasing proteolytic flora (which increase NH3 levels) & increasing saccharolytic flora besides having a laxative effect, which may contribute to the improvement of hepatic encephalopathy. In a study of acarbose in patients with low-grade hepatic encephalopathy and diabetes mellitus, besides improvement in glycemic control, treatment with acarbose resulted in a decrease in blood ammonia levels and hepatic encephalopathy.…”
Section: (H) Alfa Glucosidase Inhibitors (Agi)mentioning
confidence: 99%